2020
DOI: 10.1182/bloodadvances.2020002268
|View full text |Cite
|
Sign up to set email alerts
|

Which patients are at high risk of recurrent venous thromboembolism (deep vein thrombosis and pulmonary embolism)?

Abstract: Recurrent venous thromboembolism (VTE, or deep vein thrombosis and pulmonary embolism) is associated with mortality and long-term morbidity. The circumstances in which an index VTE event occurred are crucial when personalized VTE recurrence risk is assessed. Patients who experience a VTE event in the setting of a transient major risk factor (such as surgery associated with general anesthesia for >30 minutes) are predicted to have a low VTE recurrence risk following discontinuation of anticoagulation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 64 publications
(90 reference statements)
0
19
0
Order By: Relevance
“…This relatively high VTE recurrence risk in this cohort (23% at median follow-up of 55 months) is comparable to that found in other studies investigating unprovoked VTE. 12 This further underscores the rationale for indefinite AC among patients with unprovoked VTE. At our centers, patients with unprovoked VTE are generally placed on indefinite AC.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This relatively high VTE recurrence risk in this cohort (23% at median follow-up of 55 months) is comparable to that found in other studies investigating unprovoked VTE. 12 This further underscores the rationale for indefinite AC among patients with unprovoked VTE. At our centers, patients with unprovoked VTE are generally placed on indefinite AC.…”
Section: Discussionmentioning
confidence: 88%
“…The higher recurrence risk associated with PE (in comparison with DVT) has been noted in prior studies. 12 This study has a number of limitations largely as a result of its retrospective nature. The inclusion of only those patients who received F I G U R E 1 A Kaplan-Meier curve demonstrating recurrent VTE free survival over time for both groups is shown above.…”
Section: The American Society Of Hematology (Ash) Choosing Wiselymentioning
confidence: 98%
See 1 more Smart Citation
“…VTE recurrence following a provoked clot is approximately 3% per patient-year after stopping anticoagulant therapy 54. This risk is higher (at least 8%) in patient groups such as those with cancer or antiphospholipid syndrome and in those with no provoking cause for their PE 55…”
Section: Special Circumstancesmentioning
confidence: 99%
“…Women with a personal VTE history have a high recurrence risk during pregnancy. Women at highest risk are those with a history of unprovoked or hormone-provoked VTE [14]. In a recent pooled analysis of four cohort studies, antenatal VTE recurrence rates during pregnancy without prophylaxis were reported to be 1.1% (95% CI 0.2-5.8%), 6.4% (95% CI 3.9-10.4%), and 3.6% (95% CI 1.4-8.9%) for provoked (non-hormonal), oestrogen-related, and unprovoked VTE, respectively [14].…”
Section: Risk Factorsmentioning
confidence: 99%